Caracterização de resíduos de cigarro de apreensão e dos gases de síntese gerados durante o processo de gaseificação visando a produção de energia - Mbie, Moises Joaquim (2024)
Gasification of biomass from cigarette waste (smuggled and seized) for the production of synthesis gas and energy is an environmentally sustainable option. Thus, in this study, this fuel derived from cigarette waste was characterized, using elementary, immediate, thermogravimetric and calorimetric analyses, aiming to understand the composition, optimize the gasification process and generate synthesis gas. The characterization of the biomass showed 9.6% (m/v) moisture, 65.9% (m/m) volatiles, 12.4% (m/m) fixed carbon, 12.1% (m/m) of ash and a lower heating value (LHV) of 16.7 MJ kg–1. Next, the syngas from the gasification was characterized, both on a laboratory scale and in a semi-industrial plat. The main components of syngas at both laboratory and semi-industrial scales were CO, H2 and CH4. It was also observed that on a laboratory scale, increasing the temperature from 480 to 585 °C increased the content of combustible components from 7.6 to 20.4% (v/v) and, consequently, the LHV of 2.7 to 5.8 MJ kg–1. Tests at the semi industrial plant were inconclusive due to the permeability of the Tedlar bags used to store and conserve the synthesis gas collected at the pilot plant. However, based on laboratory results, the gasification process of seized cigarettes can be a sustainable alternative for generating synthetic gases for energy purposes.